Elevated Admission Cardiac Troponin I Predicts Adverse Outcomes of Acute Type B Aortic Dissection after Endovascular Treatment - Zhao, Kaiwen; Zhu, Hongqiao; Zhang, Lei; Liu, Junjun; Pei, Yifei; Zhou, Jian; Jing, Zaiping (Frontiers in Surgery, 2022)
Background There is a lack of evidence about the predictive role of serum cardiac troponin I (cTnI) on the long-term adverse outcomes of acute type B aortic dissection (aTBAD) patients after thoracic endovascular aortic repair (TEVAR). In this study, we identified whether cTnI was an independent risk factor of 5-year adverse outcomes for aTBAD patients after TEVAR. Methods We reviewed consecutive aTBAD patients without previous heart disease who were admitted for TEVAR. The total study population was divided into the cTnI(+) group (≥0.03 ng/mL) and the cTnI(−) group (<0.03 ng/mL) according to the time-dependent receiver operating characteristic curve analysis. The differences in clinical characteristics, operative details and clinical outcomes were compared between the two groups. Results There was no difference in age and male prevalence between the two groups. Compared with the cTnI(−) group, the incidence of chronic kidney disease was higher in patients with cTnI ≥0.03 ng/mL. In addition, the cTnI(+) group presented with more frequent premature beats and non-myocardial-infarction ST-T segment changes. In terms of laboratory examinations, white blood cell counts, neutrophil counts, serum D-dimer and serum fibrin degradation products showed an increase in the cTnI(+) group, while lymphocyte and platelet counts showed a decrease in these patients. Patients with elevated cTnI suffered from increased risks of 5-year aortic-related adverse events (hazard ratio, HR = 1.822, 95% confidence interval, CI: 1.094–3.035; p = 0.021) and all-cause mortality (HR = 4.009, 95% CI: 2.175–7.388; p < 0.001). Conclusion Among aTBAD patients without previous heart disease, preoperative elevated cTnI identified patients at an increased risk of long-term adverse outcomes after TEVAR.